ANALISIS SWOT PADA USAHA MIKRO KECIL DAN MENENGAHSTUDI KASUS PADA USAHA RUMAH MAKAN BAHARI (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) has become a common strategic tool in business development, especially in the culinary industry. Rumah Makan Bahari, a culinary business, uses SWOT analysis to shape its business strategies. This research aims to assess the restaurant's current position within the culinary sector and to identify its internal strengths and weaknesses, as well as external opportunities and threats. The results show that Rumah Makan Bahari has the potential to grow further, but an integrated approach using combined SWOT strategies is essential. For example, an SO strategy might involve hosting local events with expanded seating capacity. A WO strategy could focus on improving financial management while leveraging those local events. The ST strategy includes offering affordable prices and using fresh ingredients to stay competitive. Meanwhile, a WT strategy may involve enhancing monetization efforts to maintain competitiveness in a crowded market.